Enterprise applications and services in the finance industry : 7th International Workshop, FinanceCom 2014, Sydney, Australia, December 2014, Revised papers /: 7th International Workshop, FinanceCom 2014, Sydney, Australia, December 2014, Revised papers. (2015) - Unknown
No abstract available